Kenaf seed oil from supercritical carbon dioxide fluid extraction shows cytotoxic effects towards various cancer cell lines - Saiful Yazan, Latifah (Academic Journals, 2011)
Hibiscus cannabinus (Kenaf) from the family of Malvaceae is a valuable fiber source and medicinal plant. It has long been prescribed as traditional folk medicine in Africa and India to treat various diseases. Nevertheless, little research has been carried out on the potentials of this plant as treatment for cancer. This study was designed to determine the cytotoxicity of kenaf seed oil from two varieties (Quiping 3 and V36) extracted by supercritical carbon dioxide fluid extraction (SFE) with different combinations of pressure (bars) and temperature (°C) towards breast cancer (MCF-7, MDA-MB-231, 4T1), cervical cancer (HeLa), lung cancer (A549) and leukemic (MOLT-4) cell lines. Even though kenaf seed oil from both varieties were cytotoxic to all the cancer cells, kenaf seed oil variety V36 extracted by SFE at 600 bars 40°C (V600/40) was the strongest towards MOLT-4 and MDA-MB-231, with the IC50 values of 153.26 and 483.35 μg/ml, respectively. MOLT-4 and MDA-MB-231 cells treated with V600/40 exhibited typical characteristics of apoptosis such as blebbing, chromatin condensation and nuclear fragmentation as viewed under an inverted light microscope and a fluorescence microscope. In conclusion, V600/40 was the most cytotoxic towards the MOLT-4 and MDA-MB-231 cells in a dosedependent manner possibly via the induction of apoptosis.